PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH KEBIJAKAN DIVIDEN - Nareza Lazwardy Arafa; Mu’minatus Solichah (CV. ALIM'SPUBLISHING, 2023)
This study aims to examine the effect of Profitability and Liquidity on Firm Value either directly or through Dividend Policy as a moderating variable in finance sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. This type of research uses quantitative methods with secondary types. The population of this study is all annual financial reports of the finance sector listed on the Indonesia Stock Exchange in 2018-2020. The sample was selected using purposive sampling method and obtained 27 samples of annual financial statements. The method used in this research is Partial Least Square (PLS) through WarpPLS 7.0 software. The results show that Profitability has no significant effect on Firm Value. However, Liquidity has a significant and positive effect on Firm Value. Dividend Policy is not able to moderate Profitability and Liquidity on Firm Value.